Gender and practice : knowledge, policy, organizations - Segal, Marcia Texler; Kelly, Kristy; Demos, Vasilikie (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book contains an Open Access Chapter In 1995, the Fourth World Conference on Women: Action for Equality, Development and Peace affirmed the need to address gender inequalities and foster gender integration. Ever since, the field of gender professionals has been growing, yet the experiences, insights and data gathered have not been systematically examined and incorporated into an accessible body of knowledge. Working to address this, expert contributors demonstrate the depth and breadth of gender and practice. Including examples from Brazil, Cameroon, Ecuador, Nigeria, Sao Tome and Principe, the USA, and Vietnam, as well as chapters that take a global perspective, the research here looks at issues and activities relating to infusing gender in knowledge management, training, and practice. Including subjects such as education, agricultural production, and tourism, this volume offers a variety of perspectives that will appeal to any researcher in gender. Throughout the volume, expert practitioners situate their real-world experiences in the broader intersectional framework employed by their academic colleagues, offering policy makers, students, scholars, practitioners, and activists concrete examples of how and why gender is central to development.
Gender and practice: introduction to knowledge, policy, practice / Vasilikie Demos, Marcia Texler Segal & Kristy Kelly -- Part I: Knowledge -- 1. Exploring spaces, limits and future possibilities for feminist perspectives on knowledge management in international development and beyond / Åsa Corneliusson -- 2. Exploring the intersections and implications of gender, race and class in educational consulting / Caroline (Carly) Manion -- 3. The challenge of measuring women's economic empowerment: a critical analysis on the importance of subjective measurement and context / Magali N. Alloatti -- 4. Gender norms and their implications for banana production and recovery in West Africa / Lilian Nkengla-Asi, Deborah O. Olaosebikan, Che Vincent Simo, Sergine Ngatat, Martine Zandjanakou-Tachin, Rachid Hanna, & P. Lava Kumar -- Part II: Policy -- 5. Monitoring gender data and evaluating differential effects to reduce inequality / Anne-Françoise Thierry -- 6. Building gender research capacity for non-specialists: lessons and best practices from gender short courses for agricultural researchers in Sub Saharan Africa / Margaret Najjingo Mangheni, Hale Ann Tufan, Brenda Boonabana, Peace Musiimenta, Richard Miiro & Jemimah Njuki - OA -- Chapter -- 7. Gender politics in Latin American censuses: the case of Brazil and Ecuador / Debora Thome & Byron Villacís -- 8. A gender analysis of tourism's impact on the livelihoods of H'mong and Red D'ao women in Vietnam / Lúa Xuân Đoàn -- Part III: Organizations -- 9. Advancing women's rights from within: the story of the Alliance for Women in Medicine and Science (AWIMS) / Anne Scheer & Vidhya Prakash -- 10. Creating a global feminist organization: applying theory to practice / Angela Hartley, Karine Lepillez, Nicole Figot, Leah Goldmann, Christina Gordon, Kenneth Boÿenah Nimley & Kristy Kelly -- 11. Opportunities for feminist change at the United Nations Commission on the Status of Women / Susan Hagood Lee.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Women in development -- Research; Sex discrimination against women; Gender mainstreaming; Social Science -- Women's Studies; Gender studies: women